'An error is feedback': the experience of communication error management in crisis negotiations. (2nd January 2018) - Oostinga, Miriam S. D.; Giebels, Ellen; Taylor, Paul J.
Abstract: A range of studies have examined what should be said and done in crisis negotiations. Yet, no study to date has considered what happens when an error is made, how to respond to an error, and what the consequences of errors and responses might be on the negotiation process itself. To develop our understanding of errors, we conducted 11 semi-structured interviews with police crisis negotiators in the Netherlands. Negotiators reported making errors of three types: factual, judgment, or contextual. They also reported making use of four types of response strategy: accept, apologize, attribute, and contradict. Critically, the negotiators did not perceive errors as solely detrimental, but as an opportunity for feedback. They advocated for an error management approach, which focused on what could be learned from another person's errors when looking back at them. Suggestions for improvement of the communication error management experience in crisis negotiations are discussed.